2024
DOI: 10.1186/s12915-024-01864-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of compound eye morphology underlies differences in vision between closely related Drosophila species

Alexandra D. Buffry,
John P. Currea,
Franziska A. Franke-Gerth
et al.

Abstract: Background Insects have evolved complex visual systems and display an astonishing range of adaptations for diverse ecological niches. Species of Drosophila melanogaster subgroup exhibit extensive intra- and interspecific differences in compound eye size. These differences provide an excellent opportunity to better understand variation in insect eye structure and the impact on vision. Here we further explored the difference in eye size between D. mauritiana and its sibling species D. simulans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…We recently modeled and tested differences in vision between D. mauritiana and D. simulans resulting from the wider ommatidia of the former species. [5] As predicted, the behavioral experiments showed that D. mauritiana eyes have greater contrast sensitivity while those of D. simulans have enhanced acuity. While D. simulans is a cosmopolitan generalist, D. mauritiana is restricted to Mauritius and this finding may help to better understand their ecology and behavior, and why these differences may have been selected.…”
Section: The Functional Impact Of Variation In Eye Morphology On Visionsupporting
confidence: 58%
See 2 more Smart Citations
“…We recently modeled and tested differences in vision between D. mauritiana and D. simulans resulting from the wider ommatidia of the former species. [5] As predicted, the behavioral experiments showed that D. mauritiana eyes have greater contrast sensitivity while those of D. simulans have enhanced acuity. While D. simulans is a cosmopolitan generalist, D. mauritiana is restricted to Mauritius and this finding may help to better understand their ecology and behavior, and why these differences may have been selected.…”
Section: The Functional Impact Of Variation In Eye Morphology On Visionsupporting
confidence: 58%
“…[7] Even within the eye of D. mauritiana we have observed facet size differences up to 35%. [5] Ommatidia length also differs considerably within and between species, for example, rhabdomere length can vary from 0.46 to 1.1 mm within the eye of a dragonfly. [9,10] Differences in ommatidia number, diameter, and length affect the inter-ommatidial angles and determine how much light enters each ommatidium thus directly affecting acuity and contrast sensitivity [11][12][13] (Figure 1; Box 1).…”
Section: Superposition Eyesmentioning
confidence: 99%
See 1 more Smart Citation